Analisa Excitement dan Sincerity dengan Destination Image Sebagai Mediator di Industri Café Seaview Batam - Jessica Go; Ratih Anggraini (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This research aims to tell more deeply to the general public about the fun that exists in the industry in modern times, and educate that we must keep up with the times. The implementation of the rebranding also aims to help advance the café seaview of course in the city of batam through social media accounts. Or the method of approaching the problem is done in how to collect data from the source of respondents from the questionnaire. The expected results can be useful for cafes in increasing the number of visitors who are willing to go there and can be useful for prospective visitors and provide café references that have never been visited before.